2022
DOI: 10.13031/jash.14898
|View full text |Cite
|
Sign up to set email alerts
|

Farm Fatal Injury Trends in Illinois from 1999 to 2019

Abstract: HighlightsWe identified 510 fatal agricultural incidents in Illinois from 1999 to 2019.Tractors and roadway-related incidents were the two leading sources of fatalities.Older farmers (65 and older) accounted for the highest percentage of fatalities.Among tractor-related incidents, overturns accounted for the highest percentage.Abstract. The objective of this study was to analyze fatal injury trends and injury types in Illinois from 1999 to 2019. Data on fatal farm injuries in Illinois were collected from a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Similar to previous studies, the results of this study show that the farmer group had significantly higher rates of ICU admission, surgery, and injury-related mortality than the non-farmer group [28][29][30][31]. However, the multivariate logistic regression analysis in the unmatched sample adjusted for age, sex, inhabitant, insurance type, and year of injury showed that the adjusted OR for in-jury-related mortality was not statistically significant.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to previous studies, the results of this study show that the farmer group had significantly higher rates of ICU admission, surgery, and injury-related mortality than the non-farmer group [28][29][30][31]. However, the multivariate logistic regression analysis in the unmatched sample adjusted for age, sex, inhabitant, insurance type, and year of injury showed that the adjusted OR for in-jury-related mortality was not statistically significant.…”
Section: Discussionsupporting
confidence: 85%
“…These findings are somewhat surprising given that other studies have reported high mortality and morbidity rates among agricultural workers [4,7,10,17,25,[28][29][30][31]. A potential reason for this discrepancy could be the study design and setting.…”
Section: Discussionmentioning
confidence: 74%
“…Agriculture remains the most dangerous occupation in the U.S. (BLS, 2020) [1]. Among all agricultural injuries, tractor-related injuries are the highest [3]. Several databases track all occupational incidents, such as Ag Injury News Clippings, the Fatality Assessment and Control Evaluation (FACE), and the Bureau of Labor (BOL) statistics.…”
Section: Methodsmentioning
confidence: 99%
“…Because of more efficient machinery and systems [2]. Moreover, within all types of agricultural fatal injuries (tractor, roadway, grain bins, farm equipment, Terrain Vehicle (ATV), electrocution, animals, manure storage, and others), the number of tractor-related injuries remains high, with 213 cases from 1999 to 2019 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Production agriculture is a dangerous occupation considering high rates of fatal and non-fatal injuries (National Safety Council, 2022). Machinery and tractors are among the hazards often involved in fatal injury events based on a recent analysis of detailed incident data collected in key agricultural states (Li et al, 2022). One potential benefit of removing the human operator from a mechanized system is to reduce human exposure and associated risk that contributes to high rates of injury associated with farm machinery operation.…”
Section: Reducing Injury Risk By Reducing Operator Exposurementioning
confidence: 99%